A Linguistic Analysis of Arabic Language Errors in The Thesis Abstracts of Arabic Language and Literature Students at UIN Sunan Gunung Djati 2024 - Rifqi Muhammad Firdaus; Rohanda Rohanda; Dayudin Dayudin (UIN Sunan Gunung Djati Bandung, 2025)
This study investigates linguistic errors found in the abstracts of undergraduate theses written by students of the Department of Arabic Language and Literature, Faculty of Adab and Humanities, UIN Sunan Gunung Djati Bandung. Employing a descriptive qualitative approach, the research analyzed 50 thesis abstracts and identified 60 language errors categorized into three main types: phonological and morphological errors, morphological and syntactic errors, and syntactic and semantic errors. The findings show that the most common phonological error involves the incorrect use of hamzah, reflecting a lack of adherence to Arabic orthographic conventions. Morphological and syntactic errors consist of inaccurate verb conjugations, incorrect noun forms, and sentence structures that deviate from standard Arabic grammar. Semantic errors appear as vague or incoherent expressions, frequently resulting from syntactic mistakes and inappropriate word choices. The study identifies three principal causes of these errors: insufficient mastery of Arabic grammar and morphology, limited vocabulary prompting reliance on unchecked translation tools, and inadequate supervisory feedback from academic advisors. This research highlights the urgent need to strengthen Arabic academic writing instruction and encourages more active lecturer involvement to ensure that students' theses meet both academic and linguistic standards.